Grammar Learning with Communicative Approach for Foreign Students in BIPA Education and Training - Rizki Putri Ramadhani; Alim Harun Pamungkas (Universitas Negeri Padang, 2019)
Various opinions also took place when looking at the diverse Indonesian language learning needs of BIPA students. Not only technical language learning in the classroom, but also activities in the implementation of the program to achieve the learning needs of language and culture of BIPA students. Departing from the various problems that exist, the discussion this time will only discuss grammar that can be approved using communicative.Keywords: BIPA Learning, Grammar, Communicative Approach, Learning and Education